(untitled) (Revista de Administração, 2008)
This article reports the case of Muri Assembly Systems, founded in 1985, specialized in the development and manufacture of assembly lines for automotive industry, and it sets out an innovation strategy formulated in 2001, which has being adopted by the company since then. Its success is a consequence of the entrepreneurship of its founders; the searching for a strategic planning that captures its core competencies and the market pressures, and the definition of an innovation strategy framework that translates the knowledge acquired from the observation of the external and internal environments. As a result, Muri belongs to a minor group of Brazilian company on its industry to export its products to USA, being this a fairly indication of a successful innovation strategy framework. The report of this strategy intends to illustrate a case where the constant innovation strengthens and adds value to the company's brandmark.